Barley: Impact of processing on physicochemical and thermal properties—A review. Issue 4 (4th July 2017) - Sharma, Paras; Kotari, S. L.
ABSTRACT: Barley ( Hordeum vulgare L.) is a nutritious cereal but very little (only about 2%) of this grain is used as human food. However, it has attracted the attention of researchers and food processors in the last 15 years for its potential health benefits. It is also recognized as a functional grain because it contains high levels of β-glucan and phytochemicals. Therefore, a number of barley processing research and animal/clinical trials have been performed over the last 15–20 years. Also, health claims have been approved by a number of government agencies including the Food and Drug Administration (FDA) and the European Food Safety Authority (EFSA) about consumption of β-glucan, an important component of barley. Barley must undergo various processing steps before human consumption, which greatly affect their composition and physicochemical properties. These properties play an important role in the development of new products. Therefore, the present article reviews the literature on the effect of processing on the physicochemical and thermal properties of barley.